Music and human rights 197 notes for memory, truth and justice in Uruguay - Cannarozzo, Verónica (2023)
This work arises after knowing and listening to “Where are they?” by Luciano Supervielle, Uruguayan musician, composer and producer. The work –composed in 2021 for the March of Silence that takes place on May 20, the date on which the Uruguayan people commemorate the victims of state terrorism, repudiate human rights violations and demand for memory, truth and justice – is made up of a melody of 197 notes that represent the people who are still missing today. The article takes a historical-political journey about the situation in Uruguay after the end of the dictatorship, to inquire about the transitional justice process, the role assumed by the State, the actions promoted by civil society and the actions taken by human rights organizations. For this, regulations and reports from different civil society associations were consulted, and reports and recommendations from various bodies of the international human rights system were studied. Finally, the general characteristics of the work and the author’s statements were analyzed in light of the notion of “The open work” by Umberto Eco (1962) and the main concepts of art as activism (Expósito et al., 2011; Capasso and Bugnone, 2019).